Obesity hypoventilation syndrome, sleep apnea, overlap syndrome: perioperative management to prevent complications. Issue 1 (February 2017) - Raveendran, Raviraj; Wong, Jean; Singh, Mandeep; Wong, David T.; Chung, Frances
Abstract : Purpose of review: The prevalence of sleep disordered breathing (SDB) is increasing proportional to the prevalence of obesity. Although anesthesiologists are familiar with obstructive sleep apnea (OSA) – the most common SDB, anesthesiologists may not be aware of other SDB such as obesity hypoventilation syndrome (OHS) and overlap syndrome (combination of OSA and chronic obstructive pulmonary disease). The present review provides an update of information regarding the perioperative management of OHS and overlap syndrome. Recent findings: OHS and overlap syndrome are associated with significant comorbid conditions and more perioperative morbidity than OSA alone. Similar to OSA, most of the OHS patients are undiagnosed. An increase in serum bicarbonate level is a surrogate marker of hypercapnia. Because 90% of OHS patients have OSA, preoperative screening for OSA combined with estimation of serum bicarbonate level may detect the majority of the patients with OHS. In patients with OSA, OHS, and overlap syndrome, improvement in the perioperative outcome has been shown by initiating positive airway pressure therapy. Summary: Identification and preoperative optimization of these high-risk patients are most important. A protocol-based risk mitigation is necessary for improving the intraoperative and postoperative outcome of these patients. As a perioperative physician, anesthesiologists have a key role in the management of patients with SDB.